THE EFFECT OF GOOD CORPORATE GOVERNANCE ON FINANCIAL PERFORMANCE - Maya Sari; Tita Maulidya (Proceeding International Seminar of Islamic Studies, 2021)
The purpose of this study was to determine the effect of Good Corporate Governance on financial performance in banking companies listed on the Indonesia Stock Exchange. In this study, Good Corporate Governance is measured using the board of commissioners, the board of directors, and the audit committee, while financial performance is measured using the Return on Assets (ROA). The population used in this study were all banking companies listed on the Indonesia Stock Exchange (IDX) in 2017-2019 totaling 39 companies. Sampling was done by using purposive sampling method. And the number of companies that have become a sample is 15 companies. The data collection technique in this study uses the documentation method. The analysis technique used in this research is descriptive statistics, multiple linear regression analysis, partial test, and determinant test. The results of this study indicate that the board of commissioners has no effect on financial performance. The board of directors has no effect on financial performance. The Audit Committee has an effect on financial performance. The Board of Commissioners, the Board of Directors and the Audit Committee simultaneously influence the financial performance of banking companies listed on the Indonesia Stock Exchange. Keywords: Board of Commisioners, Board of Directors, Audit Committee, Return On Asset